1988
DOI: 10.1017/s0022112088003349
|View full text |Cite
|
Sign up to set email alerts
|

The reflection of a solitary wave by a vertical wall

Abstract: In this paper we consider the head-on collision of two equal solitary waves this being equivalent, in the absence of viscosity to the reflection of one solitary wave by a vertical wall. The perturbation expansion of the Euler equations, which lead to the Boussinesq equation at lowest order, is recast to obtain two weakly coupled KdV equations. We show analytically that the amplitude of the solitary wave after reflection is reduced. This change in amplitude is shown to be fifth order in ε, the amplitude of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 26 publications
3
28
2
Order By: Relevance
“…Another striking feature of the solitary wave reflection/collision was added by Su & Mirie (1980), who observed dispersive trailing waves behind the solitary waves after the collision from their thirdorder perturbation solution for the Boussinesq equation. Byatt-Smith (1988, 1989 made similar observations by solving two weakly coupled KdV equations. He also noticed slight changes in the heights of the solitary waves after interactions.…”
mentioning
confidence: 54%
“…Another striking feature of the solitary wave reflection/collision was added by Su & Mirie (1980), who observed dispersive trailing waves behind the solitary waves after the collision from their thirdorder perturbation solution for the Boussinesq equation. Byatt-Smith (1988, 1989 made similar observations by solving two weakly coupled KdV equations. He also noticed slight changes in the heights of the solitary waves after interactions.…”
mentioning
confidence: 54%
“…Furthermore, since these papers consider specifically the head-on collision of solitary waves, they are concerned with events which occur on relatively short time scales (i.e., time scales of O( 1 ) in our scaling). As noted in [5, p. 503], these expansions are not uniformly valid in time, and it is not clear whether or not their solutions could be controlled over time scales of O( It is worth noting that, in spite of the differences between our approach and those discussed here, Byatt-Smith [5] also finds that corrections to the amplitude of the solitary wave evolve according to the linearized KdV equation. An alternative approach to improve the KdV approximation to water waves is to work directly with a Boussinesq approximation to the water wave problem, as done by Bona and Chen in [2].…”
Section: Some Numericsmentioning
confidence: 81%
“…For the actual water wave equations, there have been a number of studies of corrections to the KdV approximation to water waves spanning the spectrum from nonrigorous asymptotic expansions [4], [5], [24], [2] to numerical solutions of the equations of motion and comparison with the KdV predictions [3], [25], [9] to experimental investigations [16], [7]. We concentrate here on the theoretical studies since they have the closest connection to our work.…”
Section: Some Numericsmentioning
confidence: 99%
“…This anomalous result is explained in Section 3.2 (see p. 17). Byatt-Smith (1987b, 1988 considered the interaction of solitary-wave solutions of the BenjaminBona-Mabony (BBM) equation and the reflection of a solitary wave from a wall by the same perturbation technique based on inverse scattering. Kkhenassamy & Olver (1992) considered the extended KdV equation of (1.1) and showed that exact solitary-wave solutions (waves with sech 2 profiles) exist only for the special parameter combination c 2 + c 3 = 30c 4 , 3c 3 = c,.…”
Section: Introductionmentioning
confidence: 99%